On the dubiousness of (some) liberal attempts to establish universally signifi cant “principles of the rationality of interaction” - Szlachta, Bogdan (Journal of Public Governance, 2014)
The author observes the currently common problem of subjectivization of liberalism as a specific carrier of rationality, set against religion understood as its previous carrier; such a subject is also to be rational, it is to personify rationality, and to indicate the substance of rational as well as normative principles that bind all subjects together. Such a solution remains in agreement not only with the attack of some liberal authors on Plato’s legacy, which delivers the substance of rationality binding every individual, but also their own proposition of “new rationality” or “reason” that would overrule or considerably limit particularistic points of view. This proposition clashes with another, also recognized as liberal, which by means of this normative rationality leads to the defence of the universal autonomy of solutions indicated byrespective individuals.